A white dwarf cooling age of 8 Gyr for NGC 6791 from physical separation processes - García Berro, Enrique (2010)
NGC 6791 is a well studied open cluster1 that it is so close to us that can be imaged down to very faint luminosities2. The main-sequence turn-off age (∼8 Gyr) and the age derived from the termination of the white dwarf cooling sequence (∼6 Gyr) are very different. One possible explanation is that as white dwarfs cool, one of the ashes of helium burning, 22Ne, sinks in the deep interior of these stars 3-5. At lower temperatures, white dwarfs are expected to crystallize and phase separation of the main constituents of the core of a typical white dwarf (12C and 16O) is expected to occur6,7. This sequence of events is expected to introduce long delays in the cooling times8,9, but has not hitherto been proven. Here we report that, as theoretically anticipated5,6, physical separation processes occur in the cores of white dwarfs, resolving the age discrepancy for NGC 6791. © 2010 Macmillan Publishers Limited. All rights reserved.